Lâminas de irrigação e doses de potásio na cultura da bananeira no terceiro ciclo de produção. - Barroso, Andréia de Araújo Freitas (2009)
The banana is the Brazilian consumers most appreciated fruit. It has relatively low cost and is rich in vitamins A, B and C, potassium and carbohydrates. It is also an important part of the economic activity for small producers and food source for most people with low incomes. However, given the lack of information on both adequate water levels for irrigation and rates of fertilizers, there is a need of greater investments in research that could provide an efficient management of water and as well as greater efficiency of application of nutrients. Thus, this study aimed to evaluate the effect of irrigation levels and potassium rates, via drip irrigation system in the culture of banana (Musa spp.) cv. Pacovan Apodi, considering the 3º cycle of production. The experiment was conducted at the experimental area of the agroempresa Frutacor in Limoeiro Norte – CE (05° 06’ S, 37º 52’ W, 151 m) in the period from june/07 the july/08. The crop was irrigated by a drip irrigation system, consisting of five emitters per plant, with nominal flow rate of 2.3 L h-1 and PS 20 mca. The experimental design consisted of a randomized blocks in a split plots design, with three replications. It was considered 5 (five) water depth (in part): 50%, 75%, 100%, 125% and 150% of the lysimeter ETc L1, L2, L3, L4 and L5, respectively and four rates of potassium (the subplot): 0%, 60%, 140% and 200% of K2O recommended by soil analysis laboratory, which correspondded to K1, K2, K3 and K4, respectively. By using the software “SAEG 9.0 – UFV”, the data were submitted to analysis of variance and then, when significant, by F test, to 5% level of probability. The regression analysis folllowed the fine-tune equations methodology considering the reffering biological meanings. The level (layer) of total water consumption in the 3º cycle was 1381.17 mm plant-1 (5.68 mm day-1), over a period of 243 days. The values of Kc for the different stages of development of the culture were 0.92 (top), 1.07 (at the middle period) and 0.98 (at the end period). Considreing the phenological variables, the irrigation levels influenced the following: circumference of the pseudostem, length and width of the 3ª leaf, plant height and total leaf area, while the rates of potassium influenced only on the circumference of the pseudostem. In relation to the phenological variables, the irrigation levels influenced the following: the circumference of the pseudostem, length and width of the 3ª leaf, plant height and total leaf area, while the rates of potassium influenced only on the circumference of the pseudostem. The concentration of K in the fruit had a significant influence for treatments, and the rate of 639 g plant-1 cycle-1 of potassium, resulted in the maximum concentration of this nutrient in the fruit, which was of 18.63 g kg-1. The water depth, for all the variables, influenced all post-harvest variable, being the maximum productivity 60 t ha-1, achieved at the water applied layer (level) of 1.563 mm cycle-1.